Gay Rebel of the Harlem Renaissance : Selections from the Work of Richard Bruce Nugent - Nugent, Bruce, 1906-1987 (Book collections on Project MUSE., 2002)
A collection of writings and artwork by Richard Bruce Nugent, an important yet heretofore obscure figure of the Harlem Renaissance.